2020
DOI: 10.1093/cid/ciaa388
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Stewardship Implementation and Antibiotic Use at Hospitals With and Without On-site Infectious Disease Specialists

Abstract: Background Many US hospitals lack infectious disease (ID) specialists, which may hinder antibiotic stewardship efforts. We sought to compare patient-level antibiotic exposure at Veterans Health Administration (VHA) hospitals with and without an on-site ID specialist, defined as an ID physician and/or ID pharmacist. Methods This retrospective VHA cohort included all acute-care patient admissions during 2016. A mandatory survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…These non-ID hospitals, which tend to be small in size and rural in location, have been shown to have antibiotic use that is similar, if not higher, than hospitals with ID support. 8,28 Ultimately, these hospitals will need to tailor their antibiotic stewardship processes according to their local needs, resources and personnel. 29 Our study has a few limitations that should be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These non-ID hospitals, which tend to be small in size and rural in location, have been shown to have antibiotic use that is similar, if not higher, than hospitals with ID support. 8,28 Ultimately, these hospitals will need to tailor their antibiotic stewardship processes according to their local needs, resources and personnel. 29 Our study has a few limitations that should be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…7 Finally, observational data from the Veterans' Health Administration (VHA) demonstrated that patients at hospitals with on-site ID support received antibiotics in a way more consistent with stewardship principles than patients at hospitals without such support. 8 Despite its benefits, many hospitals do not have access to ID expertise. Prior surveys have found that 41%-50% of US community hospitals lack an ID physician, whereas 93% lack an IDtrained pharmacist.…”
mentioning
confidence: 99%
“…In the OPTIMIST multicenter randomized study, an extended PI based on medication review, motivational interview, and follow-up after discharge reduces the readmission rate to 30 and 180 days, from 22.3 to 14.3%, and from 48.8 to 39.7%, respectively ( Ravn-Nielsen et al, 2018 ). The role of the pharmacist in the correct use of medicines is recognized in various medical specialties, such as geriatrics ( Martin et al, 2018 ), infectious disease ( Livorsi et al, 2020 ), intensive care ( Lee et al, 2019 ), surgery ( Neville et al, 2014 ), and cardiology ( Zhai et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in pharmacist‐driven ASPs for adult patients, days of therapy (DOT) with antibiotics reduced and antibiotic prescription improved 2,3 . Furthermore, the inclusion of infectious diseases pharmacists or physicians in ASPs was associated with reduced total antibiotic use and exposure among in‐patients 4 . Proper antibiotic use is important in neonates.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…2,3 Furthermore, the inclusion of infectious diseases pharmacists or physicians in ASPs was associated with reduced total antibiotic use and exposure among in-patients. 4 Proper antibiotic use is important in neonates. Prolonged antibiotic use in neonates is associated with an increased incidence of necrotizing enterocolitis, grade 3 or 4 intraventricular haemorrhage, chronic lung disease, retinopathy of prematurity, and death.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%